2020
DOI: 10.3389/fnins.2020.00353
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Silencing Ameliorates Neuroinflammation by Inhibition of p38-NF-κB Signaling Pathway in Mouse Model of Parkinson’s Disease

Abstract: Accumulating evidence suggested that neuroinflammation played a crucial role in dopaminergic neuronal death in Parkinson's disease (PD). The receptor for advanced glycation end products (RAGE), a multi-ligand receptor of the immunoglobulin superfamily, has been proposed as a key molecule in the onset and sustainment of the inflammatory response. Engagement of RAGE contributed to neuroinflammation by upregulating nuclear factor-κB (NF-κB) as well as cytokines. The aim of the present study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 54 publications
4
33
0
Order By: Relevance
“…Previously, studies have shown that ligand/RAGE interactions activate a range of intracellular signaling pathways, including the activation of MAPKs/JNK [ 17 , 35 ]. In addition, many studies have reported that LPS treatment increases the expression level of the stress associated kinases; importantly, c-Jun N terminal kinase (p-JNK) [ 24 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, studies have shown that ligand/RAGE interactions activate a range of intracellular signaling pathways, including the activation of MAPKs/JNK [ 17 , 35 ]. In addition, many studies have reported that LPS treatment increases the expression level of the stress associated kinases; importantly, c-Jun N terminal kinase (p-JNK) [ 24 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, studies have shown that ligand/RAGE interactions and activated p-JNK protein is critically involved in the upregulation of nuclear factor-kappa B (p-NF-κB; a transcription factor) [ 16 , 17 ], resulting in the production of pro-inflammatory cytokines and causing inflammation [ 37 ]. Importantly, in this regard, a considerable number of studies have also shown that systemic administration of LPS-injection increases the protein expression level of p-NF-κB and its associated neuroinflammatory markers in the initiation of neuroinflammation [ 7 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RAGE gene variants have been linked to sporadic PD in an Asian population 34,35 , indicating that RAGE might play a role in the pathogenesis of PD. Moreover, silencing of the RAGE pathway in a mouse model of PD improved neuroinflammation which causes dopaminergic neurodegeneration in PD patients 36 . This is important because the deterioration of dopaminergic neurons in the brain is believed to play a critical role in the development of PD 37 .…”
Section: Discussionmentioning
confidence: 99%